DESIGN & IMPLEMENTATION OF CONTROL SYSTEM IN HYBRID UNDERWATER GLIDER VEHICLE IN ROS ENVIRONMENT - HANIF - NIM : 13214147, MUHAMMAD
Indonesia has very wide area of ocean territory. However, this wide area of ocean territory could be wasted if their potentials are not explored and used properly. In order to utilize this potential, technology that have high endurance and high maneuverability are required in exploring this ocean territory. In response to this challenge, Hybrid Underwater Glider (HUG) that combines the advantages of Autonomous Underwater Vehicle (AUV) and Autonomous Underwater Glider (AUG) is currently being developed by the LSKK ITB research group as a further development of the previously developed AUG. One of the subsystems in the development of HUG is the control system which responsible for the movement mechanism and attitude control of the vehicle in both AUV and AUG modes. The control system on the vehicle consists of four parts : surge controller, pitch controller, buoyancy engine controller, and yaw controller. The buoyancy and pitch controls of the vehicle are sequentially referring to the finite state machine with pitch angle and depth of the vehicle as inputs to obtain movement in AUG mode. While yaw and surge controls will take responsibility of movement mechanism in AUV mode. This final project is focused on design and implementation of control system of HUG based on PID cascade mechanism. The control system is implemented in Robotic Operating System (ROS) platform in Single Board Computer (SBC) using the hardware-in-the-loop simulation (HILS) method and pool testing. The results show that the control system in the vehicle can functionally perform the input operation as desired.